Effects of dietary patterns and low protein intake on sarcopenia risk in the very old: The Newcastle 85+ study. Issue 1 (January 2020) - Granic, Antoneta; Mendonça, Nuno; Sayer, Avan A.; Hill, Tom R.; Davies, Karen; Siervo, Mario; Mathers, John C.; Jagger, Carol
Summary: Background: Sarcopenia, a progressive age-related loss of skeletal muscle mass and strength, leads to disability, falls, and hospitalisation. Individual variation in sarcopenia onset may be partly explained by lifestyle factors such as physical activity and diet. Healthy dietary patterns (DPs) have been linked to better physical functioning in older adults, but their role in sarcopenia in the very old (aged ≥85) is unknown. Aims: To investigate the association between DPs and the risk of sarcopenia over 3 years, and to determine whether protein intake influences this relationship in community-dwelling older adults from the Newcastle 85 + Study. Methods: The analytic sample consisted of 757 participants (61.2% women) who had dietary assessment at baseline. After two-step clustering with 30 food groups to derive DPs, we used logistic regression to determine the risk of prevalent and incident sarcopenia across DPs in all participants, and in those with low (<1 g/kg adjusted body weight/day [g/kg aBW/d]) and good protein intake (≥1 g/kg aBW/d). Results: We identified three DPs (DP1: 'Low Red Meat', DP2: 'Traditional British' and DP3: 'Low Butter') that varied by unsaturated fat spreads/oils, butter, red meat, gravy and potato consumption. Compared with participants in DP3, those in DP2 had an increased risk of prevalent (OR = 2.42, 95% CI: 1.15–5.09, p = 0.02) but not 3-year incident sarcopenia (OR = 1.67, 0.59–4.67, p = 0.33) adjusted for socio-demographic, anthropometry, health and lifestyle factors. Furthermore, DP2 was associated with an increased risk of prevalent sarcopenia at baseline (OR = 2.14, 1.01–4.53, p = 0.05) and 3-year follow-up (OR = 5.45, 1.81–16.39, p = 0.003) after adjustment for key covariates in participants with good protein intake. Conclusion: A DP high in foods characteristic of a traditional British diet (butter, red meat, gravy and potato) was associated with an increased risk of sarcopenia even when overall protein intake was good. The results need to be replicated in other cohorts of the very old to understand the role of DPs in sarcopenia onset and management.